KRIMINALISASI NARASUMBER KARYA JURNALISTIK DENGAN PASAL PENCEMARAN NAMA BAIK - Wahyudin, Ade; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
The pattern of legal attacks on press freedom is widespread, not only attacking journalists or the media, but also attacks by criminalizing sources. In the last five years, there have been more than five cases of reporting of sources because their statements were in the news. The Press Law does not specifically state that sources are protected by this. However, legal developments show that there are legal arguments, both through court decisions and the Press Council's assessment, which state that sources for journalistic works are protected by the Press Law. Supreme Court Decision Number 646 K/Pid.Sus/2019 is one of the decisions which states that sources for journalistic works cannot be punished because media managers are responsible. The judge's rationale is considered to be an effort to protect freedom of opinion, especially in the sector of press freedom. This research is a normative descriptive research that tries to explore the judge's considerations and analyze them with the applicable laws and regulations.Keywords: Criminalization of sources, press independence, journalistic work, protection